Analisis Kualitas Air Hasil Pengolahan Air Hujan Dengan Metode Elektrolisis Menjadi Air Bersih - Andriani, Gustin; Winarno, Dwi Joko; Kusumaastuti, Dyah Indriana (Universitas Lampung, 2020)
Water is all water that above or below the ground surface, including sea water that is on land. The need for clean water will increase, while clean water is scarce and must be paid handsomely. Meanwhile, the water source crisis is caused by the increasing need for water as a result of the growing population and land functions that can change the hydrological cycle. One way to meet human needs for clean water is by establishing the concept of rainwater harvesting, which is the concept of collecting rainwater that is stored in a reservoir and then the collected water can be used as an alternative source of water.The purpose of this study was to analyze the quality of rainwater before electrolysis and to determine the pH and TDS values of the permanent yield of rainwater and electrolysis.The results of this study are based on the results of laboratory tests showing that the overall quality of water in rainwater meets PerMenKes N0.416 of 1990. For the decreased pH and TDS values in the electrolysis process using a 1 ampere current adapter with a voltage of 300 volts has increased by 0 , 2-0.4 cm in acidic water. As well as for the area of titanium that affects the electrolysis process, the smaller the size of the titanium, the faster it will produce acid water.Keywords: water, rainwater, rainwater harvesting concept, electrolysis method, acid water.